The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1308/003588413x13511609954770
|View full text |Cite
|
Sign up to set email alerts
|

The Waterlow score for risk assessment in surgical patients

Abstract: IntroductionPerioperative scoring systems aim to predict outcome following surgery and are used in preoperative counselling to guide management and to facilitate internal or external audit. The Waterlow score is used prospectively in many UK hospitals to stratify the risk of decubitus ulcer development. The primary aim of this study was to assess the potential value of this existing scoring system in the prediction of mortality and morbidity in a general surgical and vascular cohort.MethodsA total of 101 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…The Waterlow score was first introduced in 1985 as a tool to screen for patients at risk of developing decubitus ulcers during inpatient stays. 14,15 Its use has since become accepted as a standard of care in the majority of UK hospitals. 14,19 Pressure ulcer prevention remains a priority for nursing staff and as a result, there is a strong drive to record Waterlow scores for all patients on admission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Waterlow score was first introduced in 1985 as a tool to screen for patients at risk of developing decubitus ulcers during inpatient stays. 14,15 Its use has since become accepted as a standard of care in the majority of UK hospitals. 14,19 Pressure ulcer prevention remains a priority for nursing staff and as a result, there is a strong drive to record Waterlow scores for all patients on admission.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In our institution, there is a protocol driven target of 100% of patients having their scores recorded within six hours of admission. Previous reports have suggested that the Waterlow score correlates with disease severity and outcome in acute surgical emergencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A high preoperative Waterlow score has previously been found to be associated with increased postoperative morbidity. 5 In terms of its utility for the risk algorithm, the Waterlow score looks promising as it appears to correlate with risk on initial testing. However, some discrimination will be lost through surgical case selection.…”
Section: Discussionmentioning
confidence: 99%
“…3 Data pertaining to patient demographics, indices of functional status, tumour stage, and operative and anaesthetic treatment were also included in the audit for the purpose of further model development. The Waterlow score, which has been shown to be useful as a means of predicting postoperative morbidity, 5 was tested for consideration of incorporation in a future scoring system.…”
Section: Methodsmentioning
confidence: 99%